Ultra-Permeable Dual-Mechanism-Driven Graphene Oxide Framework Membranes for Precision Ion Separations - Guo, J.; Zhang, Y.; Yang, F.; Mamba, B.B.; Ma, J.; Shao, L.; Liu, Shaomin (2023)
Two-dimensional graphene oxide (GO) membranes are gaining popularity as a promising means to address global water scarcity. However, current GO membranes fail to sufficiently exclude angstrom-sized ions from solution. Herein, a de novo “posterior” interfacial polymerization (p-IP) strategy is reported to construct a tailor-made polyamide (PA) network in situ in an ultrathin GO membrane to strengthen size exclusion while imparting a positively charged membrane surface to repel metal ions. The electrostatic repulsion toward metal ions, coupled with the reinforced size exclusion, synergistically drives the high-efficiency metal ion separation through the synthesized positively charged GO framework (PC-GOF) membrane. This dual-mechanism-driven PC-GOF membrane exhibits superior metal ion rejection, anti-fouling ability, good operational stability, and ultra-high permeance (five times that of pristine GO membranes), enabling a sound step towards a sustainable water-energy-food nexus.